The Effect of the Use of Kinetic Sand as a Stimulation Media for Fine Motor Development in Preschool Children at RA Al-Masithoh Karangploso - Imas Fideli Pragistha; Herawati Mansur; Reni Wahyu Triningsih (Pusat Unggulan IPTEK POLTEKKES KEMENKES Malang, 2022)
Fine motor skill is a developmental aspect that focuses on the ability of certain eye and limb coordination. To optimizing improvement children motor skills, stimulation is necessary. The purpose of this study was to determine the effect of the use of kinetic sand as a stimulation media for fine motor development in preschool children. This study uses a pre experimental type one group pretest posttest design. The sampling technique used was purposive sampling with a sample of 21 respondents. The results of the measurement of fine motor skills before getting stimulation most of the children is 65.2 percent included in the category of not yet capable while after getting stimulation most of the respondents is 73.91 percent were in the category of being able. Wilcoxons Signed Rank Test statistic test results show that same with 0.05. The results of the analysis show that value has a value of 0.000 or smaller than 0.05, so that H1 is acceptedd. Therefore, it can be stated that there is an effect of the use of kinetic sand as a stimulation medium for fine motor development in preschool children. It is expected that parents who have preschool children can make kinetic sand as a medium for stimulating fine motor development.